Grolier academic Encyclopedia - Grolier Incorporated (Danbury, Conn : Grolier, 1986)
A twenty-one volume encyclopedia with 32,000 entries and more than 16,000 illustrations.
Includes bibliographies and index.
Keywords: Encyclopedias and dictionaries